Increasing Students Vocabulary Mastery By Using Pictionary Game at the Tenth Grade of SMA Negeri 1 Gunungsitoli Idanoi in 2022/2023 - Novita Sari Zebua; Yaredi Waruwu; Elwin Piarawan Zebua; Trisman Harefa (Edumaspul: Jurnal Pendidikan, 2023)
Vocabulary is the basic competence that the students must reach to get other competencies like writing, reading, speaking, and listening. one of the problems that the researchers found were the students are not able to understand the whole of each word, The purpose of this research is to increase students’ vocabulary mastery by using Pictionary Game at the tenth grade of SMA Negeri 1 Gunungsitoli Idanoi in 2022/2023. The researcher used Classroom Action Research (CAR) especially quantitative method as the research method. There are two cycles which cycle consisted of two meetings each meeting consisted of planning, action, observation and reflection. The data are collected by researcher from the result of the observation, field notes and the evaluation papers. From the result of the research in each cycle, it has been showed that the students get improvement by using Pictionary Game Strategy. In Cycle I the students are failed, the average of the students’ value is 63. In Cycle II all the students are successful passing the Minimum Competence Criterion. The average of the students’ value is 89. The researchers conclude the best way to increase students’ vocabulary is using Pictionary game. Therefore, the researcher has some recommendation such as the researcher recommended the students and the teacher play Pictionary Game to increase their ability in mastering vocabulary, finally the researcher recommended all readers especially to the next researchers to explore about vocabulary that had not been explored by the researcher in the research.